PENGGUNAAN MEDIA SEBAGAI SUMBER INFORMASI PEMILU PILPRES DAN PILEG 2024 DI KALANGAN MAHASISWA PERGURUAN TINGGI KEAGAMAAN NEGERI DI PALANGKA RAYA: The Use of Media as a Source of Information of Presidential and Legislative Elections in 2024 among Students of State Religious Institutions in Palangka Raya - Safitri, Siti Noraulva; Syah, Hakim; Setiawan, Heri (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2023)
General election is a manifestation of democracy. Since Indonesia independence, general election has been carried out using various electoral systems. After the reform in 1998, the electoral system involved direct people's participation as a manifestation of people's sovereignty. General election in Indonesia is held every five years. Currently, the General Selection Commission is preparing everything regarding the general election in 2024, both the legislative and presidential elections. Information regarding general election is indeed important for the people, and the media plays an important role in providing various information regarding general election. In other words, the media acts as a means of political communication. This research aimed to describe the perspectives or opinions of students of three State Religious Institutions in Palangka Raya regarding general election information and the media used as the source of information. This research was a descriptive qualitative research, the data was collected by using in-depth interview and documentation. A total of 10 students became the key informants who were selected and determined based on purposive sampling. The results of the research showed that the majority of students thought that the media was an important source of information regarding general election, and in general, social media platforms were used as the main source of information besides the types of mainstream media or internet media. Based on the types of election information categories, the majority of informants stated that information regarding candidates and election processes or mechanisms was the information they wanted to know the most. The informants also stated that they had participated directly in general election, even though only as beginner voters because they believed that as good citizens they should have used their right to vote responsibly.